2022
DOI: 10.3390/genes13081297
|View full text |Cite
|
Sign up to set email alerts
|

Association of TCF7L2, CASC8 and GREM1 Polymorphisms in Patients with Colorectal Cancer and Type II Diabetes Mellitus

Abstract: Background: The aim of the study is to explore the association between the TCF7L2 rs7903146, CASC8 rs6983267 and GREM1 rs16969681 polymorphisms in patients diagnosed with type 2 diabetes mellitus (T2DM) and colorectal cancer. Methods: Sixty individuals were enrolled in this case-control study: thirty with colorectal cancer and type II diabetes mellitus (T2DM) and thirty healthy control individuals. Real-time PCR was used to determine the genotypes of TCF7L2 rs7903146, CASC8 rs 6983267 and GREM1 rs16969681 in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This finding is surprising, as most studies only emphasized the role of inflammatory cell infiltrate at the invasive margin in solid cancers for long-term survival, while there are no data concerning its influence on the postoperative outcomes, especially in CRC surgery [ 18 , 19 ]. Cancer-induced inflammation can be a consequence of mutations initiated by the neoplastic process or by intra-tumoral necrosis and is often potentiated by the overall proinflammatory status caused by extrinsic cancer risk factors, such as obesity, diabetes, smoking, or excessive alcohol consumption [ 20 , 21 , 22 ]. The peritumoral inflammatory response, as a marker of the interaction between the neoplastic process and the host, may influence local physiopathological processes in many ways.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is surprising, as most studies only emphasized the role of inflammatory cell infiltrate at the invasive margin in solid cancers for long-term survival, while there are no data concerning its influence on the postoperative outcomes, especially in CRC surgery [ 18 , 19 ]. Cancer-induced inflammation can be a consequence of mutations initiated by the neoplastic process or by intra-tumoral necrosis and is often potentiated by the overall proinflammatory status caused by extrinsic cancer risk factors, such as obesity, diabetes, smoking, or excessive alcohol consumption [ 20 , 21 , 22 ]. The peritumoral inflammatory response, as a marker of the interaction between the neoplastic process and the host, may influence local physiopathological processes in many ways.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA plays a crucial role in regulating gene expression and maintaining cell function ( Rizk et al, 2022 ). Accumulating evidence has demonstrated that lncRNA H19 polymorphism was closely related to the initiation, development, and prognosis of cancer ( Mitroi et al, 2022 ; Shaheen et al, 2022 ). Meanwhile, the study by Allemailem et al (2021) confirmed the possibility of H19 SNPs in diagnosis and individualized treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolytic enzymes, such as secreted aspartyl proteinases (SAPs), phospholipases (PLs) and Candida species play a role in the pathogenesis of VVC [ 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Numerous studies have reported that approximately 75% of women have experienced or been diagnosed with VVC [ 1 , 2 , 3 , 4 , 5 , 20 , 21 , 22 , 23 , 24 , 25 ]. The maximum incidence of this infection is at reproductive age, an aspect also observed in our study, the average age of the patients analyzed by us being between 27.88 years and 35.50 years.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the concentration of polymorphonuclear neutrophils (PMNs) at the level of the vaginal mucosa is a distinctive sign of an immunopathological inflammatory response that occurs in the case of acute infection with C. albicans. Yano et al are trying to explain the role played by leukotrienes in candidiasis infection, highlighting and analyzing the leukotriene receptor antagonist (LTRA), namely LTB4 (Etalocib) or LTC4, LTD4 and LTE4 (Zafirlukast or Montelukast) and have demonstrated once again the fact that these receptors reduce the inflammation of epithelial tissues [ 18 , 22 , 23 ]. Also, according to Steele & Fidel, epithelial cells play active roles in the immune responses of the vaginal mucosa thus modulating the antimicrobial activity and the production of cytokines and chemokines in response to microorganisms [ 21 ].…”
Section: Discussionmentioning
confidence: 99%